Comparison of the effects of remimazolam and propofol on postoperative delirium in elderly surgical patients: a meta-analysis - Jiayu Huang; Zhenke Xiao; Junming Lao; Lingli Pan; Zhou Chen; Zehua Lin (BMC Anesthesiology)
Abstract Objective This meta-analysis evaluated the effectiveness of remimazolam compared to propofol in preventing postoperative delirium among elderly surgical patients. Methods We systematically searched PubMed, CNKI, Cochrane Library, Web of Science, Embase, Wangfang, and VIP for randomized controlled trials (RCTs) comparing remimazolam and propofol for postoperative delirium prevention in elderly surgical patients (last search: July 27, 2024). Data were analyzed using Stata 15.0. Results Eight randomized controlled trials (2,013 participants; remimazolam = 1,034, propofol = 979) found no significant differences in postoperative delirium incidence [RR = 0.67,95%CI(0.45–1.01)], severity [WMD=-0.28,95%CI(-0.61-0.04)], or duration [WMD=-0.06,95%CI(-0.15-0.03)], nor in postoperative pain VAS scores [WMD=-0.08,95%CI(-0.18-0.02)]. remimazolam significantly reduced postoperative hypotension risk compared to propofol [RR = 0.48,95%CI(0.29–0.80)], demonstrating improved safety. Conclusion This meta-analysis demonstrates comparable efficacy between remimazolam and propofol in preventing postoperative delirium, with remimazolam demonstrating superior safety through significantly lower postoperative hypotension rates.